Accounting treatment of tax credits arising from the exclusion of ICMS from the PIS and COFINS calculation base of publicly traded companies - Schmidt, Douglas Willian Nascimento; Cescon, José Antonio; Brunozi Junior, Antônio Carlos; Ferreira, Julio César (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: The objective of the study was to demonstrate the accounting treatment adopted by companies listed on B3, Novo Mercado, regarding the dispute over the exclusion of ICMS from the PIS and COFINS calculation basis, as well as demonstrating the change in accounting treatment, following the decision of the Federal Supreme Court, favorable to companies in 2017, modulated in 2021. Methodology: This research has a descriptive, documentary, and qualitative nature. The initial sample was composed of the financial statements (Balance Sheet, Income Statement for the Year and Notes and Explanations) of 80 companies in the Novo Mercado segment of Brazil, Stock Exchange and Counter - B3, between 2018 and 2021 (including). After initial analysis, companies that did not present information on tax credits arising from the exclusion of ICMS from the PIS and COFINS Calculation Base were excluded, resulting in a final sample of 34 companies. In analyzing this data, Excel® spreadsheet systems and PDF readers (Foxit® and Adobe®) were used to search for information on the accounting treatment of credits arising from the exclusion of ICMS. Results: The results demonstrate that there was a change in the accounting treatment of recording these tax credits. In 2017, 8/9; in 2018 12/18; in 2019 5/27; in 2020 5/29, and in 2021, 1/34 companies registered as Contingent Assets. The change in treatment began in 2018, with 6/18; in 2019, 22/27; In 2020, 24/29, and in 2021 33/34 companies registered as Assets to be Recovered. It was also found that credits arising from the exclusion of ICMS from the PIS and COFINS calculation base had a positive impact on the results presented by companies in the years 2018 to 2021. Contributions of the Study: The main contribution of the study consists of showing that companies, faced with legal uncertainty in the country, make different accounting registration/recognition options when it comes to tax rights/obligations, as the subject supporting the object of the study has been discussed for almost decades until its outcome was favorable to companies in 2021.